Promoting Social Media Engagement Via Branded Content Communication: A Fashion Brands Study on Instagram - Castillo-Abdul, Bárbara (2022)
Social networks have become crucial communication channels for brands through awareness, engagement, and word of mouth. Instagram is firmly positioned as a direct gateway between brands and consumers, as it became the fifth most-used social network globally in 2021. As such, branded content is expected to increase the brand’s likability, by capturing the interest and attention of the consumer, which could differ depending on what social media platform is used. This study aims to analyze whether there is a relationship between the branded content published on the Instagram profile of luxury brands (Manolo Blahnik and Loewe) and the interactions of and with its followers, focusing on branded content communication associated to industrial, social responsibility, and commercial issues. A correlational study is presented using a quantitative methodology to test the hypotheses through an ANOVA analysis. The results show which type of content is more productive on Instagram’s social network profile, helping diffusion of the firm, as it provokes more reactions from followers when using branded content related to social responsibility. It is also worth noting the extent of the interactions that branded content shows within the brand, whose influence is detected not in averages but in reach. The study’s conclusions allow us to affirm that branded content directly impacts brand reputation, generating positive engagement in all the cases analyzed. The study contributes to a better understanding of the branded content effect on consumers.